Economic value estimation of Sontoh Laut mangrove ecosystem, Surabaya, Indonesia - Nor, Azril Reza Tri Septian; Firmansyah, Iqbal Putra; Kurniawan, Fadila Angga; Masyitoh, Dewi Laela (Journal of Marine Resources and Coastal Management, 2022)
Mangrove ecosystems provide many benefits both indirectly (non-economic value) or directly (economic value) to human life. Mangrove ecosystem has a role as nursery ground, feeding ground, and spawning ground for a number of associated biotas. Mangroves also play the role of pollutant absorbers and abrasion prevention. This study aims to estimate the total economic value (TEV) of Sontoh Laut mangrove ecosystem in Tambak Sarioso Village, Asemrowo District, Surabaya, Indonesia. Using total economic valuation methodology, the economic value of Sontoh Laut mangrove ecosystem is estimated IDR 7,976,672,305. The value of direct use as milkfish ponds, salt ponds, and tourism in the amount of IDR 1,551,435,267. Indirect use value as feeding, nursery, and spawning ground and coastal protection in the amount of IDR 4,921,379,060. Option value (biodiversity), existence value, and bequest value are IDR 2,026,451, IDR 1,346,688,000, and IDR 155,143,526, respectively. The results of the study show that the mangrove resources must be managed based on sustainable basis in line with balanced economic development.